Disciplinary climate, opportunity to learn, and mathematics achievement: an analysis using doubly latent multilevel structural equation modeling. Issue 3 (3rd July 2022) - Wang, Faming; Liu, Yaping; Leung, Shing On
ABSTRACT: Disciplinary climate and opportunity to learn (OTL) are considered as effectiveness-enhancing factors that can improve mathematics achievement. In this study, we investigated whether the school-level aggregation of student-reported OTL could yield reliable and valid measures, and then explored the relationships among disciplinary climate, OTL, and mathematics achievement at both school and student levels. Doubly latent multilevel structural equation modeling was adopted to analyze data from 63 countries/economies measured in the Programme for International Student Assessment (PISA) 2012. Three key findings emerged: (1) both disciplinary climate and OTL were reliable constructs when used at the school level, (2) disciplinary climate and OTL had positive effects on achievement at the school level, and OTL mediated the influence of disciplinary climate on achievement, and (3) OTL was positively associated with student achievement at the student level. Methodological and practical implications were discussed.